The local matters: Working with teachers to rethink the poverty and achievement gap discourse - Emery, Carl; Dawes, Louisa; Raffo, Carlo (Education Policy Analysis Archives, 2022)
This paper is concerned with the current achievement gap policy agenda and associated material and discursive power that shape teachers’ work in schools with high child poverty rates. More specifically, it explores how a university/school research collaboration – Local Matters – can disturb such forms of subjectivation by enabling educators to resist such policy agendas/discourses by drawing on locally contextualized knowledge and place-based evidence. Based on fieldwork undertaken over the past three years at more than 40 schools with 84 teachers across five Local Authority regions in Northern England, we provide a critical discourse analysis of a series of semi structured interviews and focus group activities of those who participated in the project. Based on an interdiscursive and linguistic analysis of the data we show how educators wrestle with the tensions between attempting to enact a social justice, collaborative and a democratic pedagogic approach and dealing with policy requirements that focus on the achievement gap problem and associated ‘what works’ discourse solution. Through the enactment of the program we show how educators, in collaboration with activist researchers, can develop forms of principled resistance that shake up and unsettle dominant forms of child poverty practice and discourses in schools.